From 3D to 4D: integration of temporal information into CT angiography studies - Haubenreisser, Holger; Meyer, Mathias; Riester, Thomas; Schönberg, Stefan; Henzler, Thomas (European journal of radiology, 2015)
CT angiography is the current clinical standard for the imaging many vascular illnesses. This is traditionally done with a single arterial contrast phase. However, advances in CT technology allow for a dynamic acquisition of the contrast bolus, thus adding temporal information to the examination. The aim of this article is to highlight the clinical possibilities of dynamic CTA using 2 examples. The accuracy of the detection and quantification of stenosis in patients with peripheral arterial occlusive disease, especially in stadium III and IV, is significantly improved when performing dynamic CTA examinations. The post-interventional follow-up of examinations of EVAR benefit from dynamic information, allowing for a higher sensitivity and specificity, as well as allowing more accurate classification of potential endoleaks. The described radiation dose for these dynamic examinations is low, but this can be further optimized by using lower tube voltages. There are a multitude of applications for dynamic CTA that need to be further explored in future studies.
Gesehen am 13.09.2017